2014
DOI: 10.9755/ejfa.v26i8.17794
|View full text |Cite
|
Sign up to set email alerts
|

Mendelian segregation pattern and expression studies of insecticidal gene (cry1Ac) in insect resistant cotton progeny

Abstract: The progenies of transgenic lines Bt-14 and Bt-17 developed as an independent transformation event from a local cotton variety CIM-482 harboring two insecticidal genes (cry1Ac & cry2a) were evaluated to determine resistance against lepidopterans, mainly Helicoverpa armigera L. under field conditions. The standard molecular techniques, i.e. polymerase chain reaction (PCR), enzyme-linked immunosorbent assay (ELISA) and western dot blot were used to confirm gene presence and expression level of transformed Bt gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 42 publications
2
1
0
Order By: Relevance
“…Hence not all the primary transformants were positive at this stage; escapes were recorded that probably avoided selection pressure (McCormick et al 1986). Our results are in line with several research workers who confirmed the integration of foreign DNA in cotton genome through PCR and ELISA (Schrammeijer et al 1990;Cousins et al 1991;Tohidfar et al 2008;Khan et al 2011;Bakhsh et al 2012;Hussain et al 2014).…”
Section: Discussionsupporting
confidence: 88%
“…Hence not all the primary transformants were positive at this stage; escapes were recorded that probably avoided selection pressure (McCormick et al 1986). Our results are in line with several research workers who confirmed the integration of foreign DNA in cotton genome through PCR and ELISA (Schrammeijer et al 1990;Cousins et al 1991;Tohidfar et al 2008;Khan et al 2011;Bakhsh et al 2012;Hussain et al 2014).…”
Section: Discussionsupporting
confidence: 88%
“…An explanation for these results would be the total protein production goes down towards the latter part of plant growth. These results are in concurrence with the earlier studies in Bt cotton [28][29][30][31][32][33][34][35][36][37][38][39] which reported a decline in expression of other Bt protein(s) during the crop growth period. Besides, decrease in expression of Bt protein gene at later developmental stages was also correlated with changes in the methylation state of CaMV35S promoter region [28,40].…”
Section: Discussionsupporting
confidence: 92%
“…Many studies report that the mode of transgene inheritance follows directly a Mendelian segregation pattern [ 54 57 ] In maize, Duncan et al [ 58 ] reported that after GM traits were introgressed into landrace maize varieties the transgene segregated like other endogenous genes, following Mendelian principles,. In contrast, non-Mendelian segregation of transgenes has been reported in studies on rice [ 59 ], soybean [ 60 ], tobacco [ 61 ], wheat [ 62 ] and cotton [ 63 , 64 ]. In a study with white clover, non-Mendelian segregation was found in F2 populations and the distortion was influenced by genetic background [ 65 ].…”
Section: Resultsmentioning
confidence: 99%